Cognitive impairment and anxiety are prevalent in kidney transplant recipients - Aleksandra Golenia; Piotr Olejnik; Norbert Żołek; Ewa Wojtaszek; Jolanta Małyszko (Karger Publishers, 2023)
Introduction. Cognitive impairment (CI) is common in end-stage kidney disease (ESKD), including kidney transplant recipients. Patients with cognitive problems may find it difficult to comply with medical recommendations after kidney transplantation (KT), which can be the cause of many complications, poorer prognosis, and increased hospitalization rates after transplantation. Additionally, some patients after KT may experience depression and anxiety, which are prevalent comorbidities in patients with ESKD. Methods. In this single-center, cross-sectional study, we included 56 consecutive adult patients after KT. Cognitive function were assessed using the Addenbrooke Cognitive Test III (ACE III). In addition, all patients were screened for depression and anxiety using the Hospital Anxiety and Depression Scale (HADS). The impact of immunosuppressive therapy and other disease-related variables on cognitive function were also assessed. Results. A total of 56 KT patients, with a mean age of 50.3 ± 11.7 years, transplanted ≤ 35 months ago were included in the study. The prevalence of CI was 30%. Compared with cognitively unimpaired patients, patients with CI scored significantly lower in all cognitive domains. Furthermore, better cognitive functioning after KT was significantly associated with more years of schooling. We found no significant correlation between CI and age at assessment, duration of dialysis before KT, creatinine levels, creatinine clearance, uric acid levels, hemoglobin levels, comorbid cardiovascular diseases as well as immunosuppressive therapy. In addition, the prevalence of depression and anxiety in screening tests was 12.5% and 27%, respectively, and patients receiving higher daily dose of prednisone had higher HADS scores on both the depression and anxiety subscales (not statistically significant). Discussion/Conclusion. Cognitive disorders is a relevant issue in kidney transplant recipients. There might be many factors, both before and after KT, that have a negative impact on cognition. Therefore, further research is needed to increase knowledge about the course and profile of cognitive function after KT.